PARSING THE SIGNIFICANCE OF THE TRANSFORMATIONAL LEADERSHIP IMPLEMENTATION TO ISLAMIC EDUCATIONAL INSTITUTIONS - Syamsuddin Syamsuddin; Binti Maunah (Perkumpulan Manajer Pendidikan Islam (PERMAPENDIS) Indonesia, 2020)
The aim of this article is to parse the significance of the implementation of transformational leadership in Islamic educational institutions. Research libraries are the methods used in this research. The results of the parsing of the concept and theory of characteristics and components of transformational leadership are found that transformational leadership has positive implications for the various critical variables that contribute to the advancement of Islamic Educational institutions. For example, able to build awareness of vision together, build trust, constructing organizational citizenship behaviour, developing motivation, more empowerment, build self-efficacy, and learning organization. It can be on the theoretical basis that to improve the quality of Islamic education institutions hence the importation of transformational leadership is absolutely done.